Entrepreneurial finance and the Russian war against Ukraine: A survey of European venture capital and private equity investors - Helmut Krämer-Eis; Jörn Block; Antonia Botsari; Frank Lang; Solvej Lorenzen; Walter Diegel (European Investment Fund (EIF), 2023)
The EIF VC Survey and the EIF Private Equity Mid-Market Survey (the largest combined regular survey exercises among General Partners on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2022 waves of these two surveys and examines how the Russian offensive war against Ukraine that started in 2022 affected VC and PE mid-market fund managers and their portfolio companies. The results show that the war - and the related consequences - had a strong impact on the two investor types and on entrepreneurial finance in Europe, inter alia regarding the challenges faced, investment strategies as well as LPs' reaction to the changed macroeconomic and geopolitical environment. The results have implications for VC and PE investors and for policy-makers due to the importance of the entrepreneurial finance sector for supporting entrepreneurship and innovation in Europe.
Keywords: 330